The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1037/mil0000077
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Heterogeneity of Daytime and Nighttime Symptoms of Posttraumatic Stress in Combat Veterans With Insomnia

Abstract: Daytime and nighttime symptoms of posttraumatic stress disorder (PTSD) are common among combat veterans and military service members. However, there is a great deal of heterogeneity in how symptoms are expressed. Clarifying the heterogeneity of daytime and nighttime PTSD symptoms through exploratory clustering may generate hypotheses regarding ways to optimally match evidence-based treatments to PTSD symptom profiles. We used mixture modeling to reveal clusters based on six daytime and nighttime symptoms of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…PTSD treatments require effective advanced learning and memory functions [28]. Early interventions for sleep may offer less mental health stigma compared to treatment for PTSD, reduce daily symptoms, and build therapeutic rapport and overall stability prior to engaging in more challenging trauma-focused therapies [52]. Further studies are needed to determine the optimal temporal relationship between sleep and PTSD treatments.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD treatments require effective advanced learning and memory functions [28]. Early interventions for sleep may offer less mental health stigma compared to treatment for PTSD, reduce daily symptoms, and build therapeutic rapport and overall stability prior to engaging in more challenging trauma-focused therapies [52]. Further studies are needed to determine the optimal temporal relationship between sleep and PTSD treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified three distinct symptom profiles related to sleep, presence or absence of parasomnia symptoms, and a continuum of daytime PTSD symptom severity. All three profiles included poor sleep quality [62]. These preliminary data support viewing sleep and trauma-related symptoms on a spectrum and evaluating treatment effects as a function of symptom profiles rather than diagnoses.…”
Section: Rdoc Framework-based Correlates Of Trauma and Sleepmentioning
confidence: 58%